Research methodology a step-by-step guide for beginners - Kumar, Ranjit (Sage Publications Ltd, 2019)
Eight steps, two pathways, one book. The Fifth Edition of the bestseller Research Methodology has reimagined, redesigned, and fully renovated how a textbook can help students achieve success in their methods course or research project. Eight steps: Foolproof for any beginner researcher, the book breaks the process of designing and doing a research project into achievable stages. It delivers students from research problem to their written research report at the pace they need, with clear explanations, DIY tasks and study skills support. In a new landscape format it presents figures, models and visualizations elegantly, so they don't break over a page, making even complex concepts easier to understand. Two pathways: With an innovative, beautiful design, regular progress checkpoints have been built into the book and its online resources. As students proceed through the 8 steps, each chapter provides regular opportunities for students to check understanding or give themselves a challenge. Each pathway then gives them the resources they need. With this one book, every student gets what they need to succeed. It is the perfect essential text for students and beginner researchers across the social sciences.